Consumer Perception Regarding Plastic Money – Changing Dimension and Its Impact: The impact of plastic money on consumer behavior and the banking system in Bangladesh (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Technology has radically changed every one of the segments including the money related division, and the exchanges in the saving money framework have additionally experienced a surprising change. The conventional idea of installment through money is supplanted by the Visas or the check cards called 'plastic cash' that individuals are utilizing to attract money or to make buys. This specific research concentrates on the recognition about the acknowledgment of plastic cash, its ease of use and moderateness while they are having an effect on its inclination of utilization in Bangladesh. Information have been gathered from 202 respondents utilizing a semi-organized poll covering understudies, taxpayer driven organization holders, representatives of private organizations, and specialist. It is discovered that a large portion of the respondents are utilizing plastic money as a rule for shopping and global buys, and furthermore to purchase costly items. With a specific end goal to recognize the idle factors in regards to the impression of utilizing plastic cash, factor investigation has been fused. Factor examination separated three dormant elements, to be specific, persuasive factor for utilizing plastic cash, useful factor of utilizing plastic cash, and issues in utilizing plastic cash. Corroborative factor investigation has additionally been done keeping in mind the end goal to get the level of impact of the watched factors on the separated variables. What's more, it is discovered that among the persuasive factors, individuals are for the most part affected for utilizing plastic money since they think it includes an incentive in their way of life. Secure exchange is the most useful reason of utilizing plastic money as per the respondents. The issues of utilizing plastic money as found through corroborative factor investigation, are inaccessibility of money in ATM (Automated Teller Machine) corners, inaccessibility of technology of installment through plastic money in buy focuses, and the mechanical difficulties looked by the card holders.